Beyond the blur: Scopolamine's utility and limits in modeling cognitive disorders across sexes – Narrative review - Jagielska, Angelika; Sałaciak, Kinga; Pytka, Karolina (Ageing research reviews, 2025)
Scopolamine, widely regarded as the gold standard in preclinical studies of memory impairments, acts as a non-selective antagonist of central and peripheral muscarinic receptors. While its application in modeling dementia primarily involves antagonism at the M1 receptor, its non-selective peripheral actions may introduce adverse effects that influence behavioral test outcomes. This review analyzes preclinical findings to consolidate knowledge on scopolamine's use and elucidate potential mechanisms responsible for its amnestic effects. We focused on recognition, spatial, and emotional memory processes, alongside executive functions such as attention, cognitive flexibility, and working memory. The cognitive effects of scopolamine are highly dose-dependent, influenced by factors such as species, age, and sex of subjects. Notably, scopolamine rapidly induces observable memory impairments across species, from fish to rodents and primates, often with deficits that can persist for days. However, the compound's broad action on muscarinic receptors and its peripheral side effects, including pupil dilation and reduced salivation, complicates result interpretation, particularly in tasks requiring visual discrimination or food intake. The review also highlights scopolamine's translational value in modeling dementia and Alzheimer’s disease, emphasizing the importance of considering individual factors and task-specific designs. Despite its widespread use, scopolamine’s limited specificity for cholinergic dysfunction and inability to fully mimic the complex pathophysiology of cognitive disorders like Alzheimer’s and Parkinson’s disease point to the need for complementary models. This review aims to guide researchers in using scopolamine for modeling cognitive impairments, ensuring attention to factors impacting experimental outcomes. •Scopolamine effectively induces memory impairments across species, aiding dementia modeling.•Despite its non-selectivity, scopolamine is widely used for modeling cholinergic-related memory deficits.•Scopolamine’s effects on cognition differ with species, sex, and hormonal cycles.•Peripheral actions of scopolamine may complicate behavioral test outcomes.